Cover Feature: Recent Advances in Palladium‐Catalyzed Carboxylation with CO2 (Eur. J. Org. Chem. 6/2018). Issue 6 (23rd January 2018) - Song, Jian; Liu, Qing; Liu, Hui; Jiang, Xuefeng
Abstract : The Cover Feature shows carbon dioxide fixation by palladium catalysis. Palladium, playing as a master of magic, can introduce carbon dioxide to various substrates, delivering a wide variety of valuable molecules. Due to economic and environmental requirements, methodologies for carboxylation are highly desired to proceed with readily available chemicals. Therefore, the exploration of milder conditions for carboxylation still is a great challenge for organic synthetic chemists. More information on recent advances in palladium‐catalyzed carbon dioxide fixation can be found in theMicroreview by H. Liu, X. Jiang et al.